SCIENTIFIC-METHODICAL APPROACHES OF VALUE THEORY FOR MARKETING POSITIONING OF MEDICAL SERVICES - STADNYK, Valentyna; YOKHNA, Vitaliy; LIUBKA, Vitalii; JAREMISHYN, Jaroslav (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The purpose of the study is to clarify the definition of "medical service" from the point of view of the theory of value for the relevant emphasis on the defining characteristics of its quality, which will serve to increase the effectiveness of the marketing positioning of the services of medical institutions in market conditions. The article substantiates the author's position that it is appropriate to take the value theory methodology as the basis of marketing positioning in the market of medical services. Based on a value-oriented approach in management theory, as well as based on the essence and goals of marketing positioning as a tool for influencing consumer behaviour, the article analyses the key characteristics of marketing positioning strategies in relation to market offers of medical services. Priority in this positioning of quality issues is emphasized. Emphasis is placed on the fact that in the medical field the concept of quality has the most subjective dimension of all possible types of services in other areas of human activity, since the quality result from treatment depends not only on the qualification of the doctor and the perfection of treatment protocols, but also on the general state of health. I of a specific patient and his psychological state. Therefore, an important characteristic of the quality of medical services in their marketing positioning should be the quality of service. In the work, on the example of family medicine services, other characteristics of their quality are highlighted, the specificity of which affects their consumer value. It is emphasized that such differences must be taken into account and properly broadcast to the target audience for their positive perception.
Keywords: value-oriented approach in management; consumer value; marketing positioning strategy; subjectivity of quality perception; consumer interest